Optimisation of aquifer parameters: a case study from Bheri Terai area, mid western Nepal - Kunwor, Moti Bahadur (Journal of Nepal Geological Society, 1998)
For the study of groundwater potential in any area, it is necessary to determine aquifer parameters as correctly as possible. The most effectively and popularly used tools in the field by groundwater geologists and engineers till today is old conventional curve techniques. A new approach is given to refine the aquifer characteristics by computer-assisted numerical techniques. The computer-assisted techniques were used in the Bheri Terai area (Banke/Bardiya), mid western Nepal with an objective of studying the aquifer parameters more accurately with reference to the prevailing hydrogeological condition. Keeping in view of the nature and types of aquifer, an optimisation based model developed by Jageshwar (1985) has been adopted for estimation of aquifer parameters. The aquifer parameters in the study area have been evaluated by using both curve procedure and computer assisted numerical techniques. Parameters are optimised by minimisation of sum of the square of residues between computed and observed drawdown. The starting values of parameter for optimisation were generally assigned as per the available graphical procedures. The applicability of the model to the field data has been demonstrated by using the existing test pumping data of Bheri Terai area (GWRDB, 1979). The purposed model for the analysis of test pumping data yields significantly better reproduction of time drawdowns. The results of analysis of test pumping data indicate confined and leaky confined nature of deep aquifer. Majority of leaky aquifers show a declining nature of piezometric head in the overlying aquifer while, some of the confined aquifer shows finite nature in areal extent due to the presence of barrier boundary (most probably impervious clay?).